METHODS AND MEANS OF TEACHING USING IMMERSIVE PROGRAMS IN CLASSROOM AND EXTRACURRICULAR ACTIVITIES IN THE RUSSIAN LANGUAGE (Intent Research Scientific Journal, 2023)
The work is devoted to the problem of intensification of teaching Russian as a foreign language in the process of formation and development of the lexical competence of students. The role of educational dictionaries of various types is emphasized